The vulva : a practical handbook for clinicians - Fischer, Gayle, 1953-; Bradford, Jennifer, 1960- (Cambridge : Cambridge University Press, 2016)
This practical handbook reviews the important, but complex, area of vulval disease and will help busy clinicians help their patients. The authors have a fresh and evidence-based approach to dealing with everything from common to rare vulval conditions. Their take on vulvodynia and dyspareunia represents an important breakthrough in the understanding of vulval pain. The first edition of this book appeared in 2010, at a time when there was very little published evidence on vulval disease. The entire text has been updated in line with modern practice. A reading list and references are included at the end of each chapter. There is further information on management, particularly in the field of long-term treatment of lichen sclerosus and on newly described conditions. The text is designed for gynaecologists and dermatologists but will also be readily understandable to primary care and family practice physicians, nurse practitioners and others working in women's health.
Title from publisher's bibliographic system (viewed on 02 Nov 2016).
Keywords: Vulva -- Diseases